Transboundary viral diseases of pigs, poultry and ruminants in Southeast Asia: a systematic review - Thi Ngan Mai; Thanh Trung Nguyen; Sinh Dang-Xuan; Hung Nguyen-Viet; Unger, Fred; Hu Suk Lee (Informa UK Limited, 2024)
Livestock is a strategic part of the small-farm economy in Southeast Asia’s society, providing food income, clothing, fertilizer, and draught power. However, incidences or outbreaks of transboundary animal diseases (TADs) are due to converging factors such as the natural hazards’ aftermath, climate change, deforestation, urban growth, changing production conditions, and market chains. Therefore, this affects productivity and impacts farmers’ livelihoods with small holdings. The literature review was carried out to understand the current situation of TADs in Southeast Asia, identifying knowledge gaps to provide actions for disease control and prevention in the region. We have attempted to summarise the scientific literature in English on the prevalence data of TADs in Southeast Asia between 2011 and March 2022. Relatively few studies evaluated the distribution of TAD, where most of the studies focused on diseases that are important for international trade, such as avian influenza (AI), African swine fever (ASF), classical swine fever (CSF), foot-and-mouth disease (FMD) and Newcastle disease (ND). Traditional production systems have received little attention in such studies as they belonged to mainly smallholders. The outbreaks of ASF and lumpy skin disease (LSD) in 2019 resulted in increased research activity between 2019-2022, while the other TADs were ignored in this period. For new emerging TADs diseases such as ASF and LSD, there is only information about the first detection without prevalence information. Therefore, further epidemiological investigations are necessary to reduce the gaps in disease surveillance reporting systems and support the prevention and reduction of further outbreaks.